Reconceptualizing Warehouse Job Profiles through Transversal Skills in a Circular Economy Context - Vina Dwiyanti; Ana A; Yusep Sukrawan; Edi Supardi (Academic Bright Collaboration, 2026)
Purpose – This study aims to identify and map Transversal Skills (TS) relevant to Circular Job Profiles (CJP) in the warehousing sector in response to digitalization, automation and Circular Economy (CE) practices. The study addresses the skills gap between industry requirements and workforce competencies in circular warehousing activities such as reverse flows management, material recovery, and resource optimization. Methods – An exploratory qualitative approach was employed through two stages: a Systematic Literature Review (SLR) of 54 scholarly articles and Focus Group Discussions (FGD) involving 12 industry and academic participants. The identified skills were analyzed using thematic analysis and expert validation to develop a competency mapping matrix between TS and CJP. Findings – The study identified six key TS domains that are highly relevant to circular-oriented warehousing roles: communication, teamwork, problem-solving, self-management, digital literacy, and sustainability mindset. The findings indicate that these competencies support the adaptability, flexibility, and sustainability-oriented decision-making required for positions such as warehouse operators, reverse logistics coordinators, and sustainability supervisors. Research implications – This study is limited to qualitative competency mapping and does not measure the direct implementation outcomes of TS in warehousing performance. However, the findings provide a foundation for future quantitative validation and competency framework development. Originality – This study offers a competency mapping framework that aligns TS with CJP in the warehousing sector, contributing to the development of vocational curricula and workforce competency standards for sustainable and technology-driven logistics systems.